Assessing energy policy effectiveness in Vietnam using multi-criteria decision making - Duong, Thi Thuc Anh; Le, Viet Khai; Le, Ngoc Doanh; Vu, Minh Thai; Nguyen, Tien Dat (Center of Biomass & Renewable Energy (CBIORE), 2026)
Vietnam's energy transition is strong, and therefore, Vietnam needs a policy framework appropriate to the current context to promote this sustainable transition. This study assesses energy policy alternatives in Vietnam in order to identify the best policy strategies for sustainable energy transition by using a hybrid Multi-Criteria Decision Making (MCDM) approach. The research basically applies a DEMATEL-VIKOR framework to discuss five policy alternatives: Renewable Energy Promotion (RP), Energy Efficiency and Demand-Side Management (EE&DSM), Grid Modernization (GM), Fossil Fuel Transition (FFT), and Institutional, Regulatory and Market Reform (IR). Seven criteria, from Economic Efficiency (EE) to Policy Consistency (PC), were used for evaluation. The analysis by DEMATEL points to the Institutional and Regulatory Effectiveness (IE) as being the most crucial causal driver with the highest prominence score of 3.84 and a net causality value of 0.53. These results give direct information to the VIKOR analysis, where IR (A5) is the best compromise solution with a perfect Q-index value of 0.00 and the lowest individual regret (R-index) value of 0.08. In comparison, Fossil Fuel Transition (FFT) ranked the worst with a Q-index of 1.00. Sensitivity analysis to prove the robustness of IR as the dominant policy for all decision-making parameters (v). The results have illustrated that the energy policy of Vietnam should place more emphasis on institutional strengthening and grid modernization (Q = 0.22) than stand-alone technological deployment to ensure a stable, efficient, and equitable energy transition.